The location of the ground focus line produced by a supersonic aircraft - MAKAREWICZ, Rufin (Archives of Acoustics, 1977)
An aircraft flying at a speed higher than that of the propagation of sound produces a supersonic boom, and it has been observed that certain changes in the flight velocity or direction are accompanied by focussing the boom. In this paper procedural algorithms are presented which permit determination of the points on the Earth's surface at which this phenomenon occurs, for any manoeuvre (in section 2) and for accelerated rectilinear flight (in section 3).